ANTI-INFLAMMATORY EFFECT OF LEAF ETHANOL EXTRACT OF CAT'S KUMIZE (ORTHOSIPHON STAMINEUS BENTH) IN MALE WHITE RATS OF WISTAR STRAINS - Wilson Samosir; Shofian Syarifuddin (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2020)
The cat's whiskers plant is empirically used by the community for the treatment of gout and rheumatism. This research was conducted with the aim of knowing the anti-inflammatory power of cat's kumis (Orthosihon stamineus Benth) leaf extract. This study was a quasi-experimental study with a one-way completely randomized design. Kumis Kucing leaf extract was extracted using 70% ethanol. A total of 25 male wistar rats aged 2-3 months, weighing 150-200g were divided into 5 groups. Each group was treated orally with distilled water (negative control), diclofenac sodium 2.25 mg/kg BW (positive control). Kumis leaf ethanol extract tested at doses of 123, 245 and 490 mg/kgBB. Treatment 1 hour before the feet of rats were inflamed with 1% sublantar carrageenin. Measurements of the rat's foot volume were carried out every 0.5 hours for 6.5 hours. The obtained average edema volume curve is used to calculate AUC (Area Under The Curve) and the obtained AUC is used to calculate DAI (Anti-Inflammatory Power). The AUC and DAI data were tested statistically with one way Anava and followed by LSD with a 95% confidence level. The results showed that the ethanol extract of Kumis Kucing leaves had an anti-inflammatory effect on male white rats of the Wistar strain. Kumis Kucing ethanol extract at doses of 123, 245 and 490 mg/kg BW yielded 33.11%; 52.64% and 64.12% respectively. The results showed that the ethanol extract of Kumis Kucing leaves had an anti-inflammatory effect on male white rats of the Wistar strain. Kumis Kucing ethanol extract at doses of 123, 245 and 490 mg/kg BW yielded 33.11%; 52.64% and 64.12% respectively. The results showed that the ethanol extract of Kumis Kucing leaves had an anti-inflammatory effect on male white rats of the Wistar strain. Kumis Kucing ethanol extract at doses of 123, 245 and 490 mg/kg BW yielded 33.11%; 52.64% and 64.12% respectively.